A conceptual framework for assessing electronic banking continued use - Kartiwi, Mira; Rfieda, Ali; Gunawan, Teddy Surya (IEEE, 2013)
The development and advancement of electronic banking (e-banking) had raised the level competitiveness in the market for financial products and services. More and more banks and other financial institutions adopted such technology to improve service quality and enhance customer satisfaction and loyalty. Despite the increasing number e-banking users globally, little is known on how this technology can help banks to retain customers. Furthermore, it is only recently that researchers have started to understand the importance of consumers’ continued use. Therefore, it is the aim of this paper to propose a framework based on an extensive review of current literature in related areas of e-banking domain and continued use. The main benefits of the proposed framework are towards understanding factors that may influence the e-banking continuance usage.